Density in the Suburbs: Families with Children Adapting to Living in a Medium Density Social Housing Development. Issue 4 (2nd October 2021) - Opit, Simon; Kearns, Robin; Witten, Karen; Fergusson, Emma
ABSTRACT: Medium-density housing (MDH) is posited as a solution to providing greater housing affordability. Yet, higher-density housing is often considered unsuitable for children. Our study investigates the experiences of families living in a new MDH development designed for affordability and sited in a suburban location. Findings highlight trade-offs made by families moving into higher density residential environments and the positive effects of a supportive social environment and flexible dwelling designs integrated with communal spaces. Also evident is the enduring challenge of car dependence and the need to address the interface between developments and surrounding amenity and public transit environments. The research provides an example of positive experiences of families living in MDH that runs counter to conventional expectations.